Early-strength magnesium phosphate slag cement mortar and preparation method thereof
By using raw materials such as superfired magnesium oxide and potassium dihydrogen phosphate, early-strength magnesium phosphate slag cement mortar with specific ratios, the problem of insufficient early strength and flexural strength in the existing technology is solved, and efficient and environmentally friendly cement mortar preparation is achieved.
Patent Information
- Application Number
- CN202510094284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
In the development of early-strength magnesium phosphate cement mortar, it is difficult to take into account early strength, high flexural strength and environmental protection, and there is a problem of insufficient controllable settling time.
The premature magnesium phosphate slag cement mortar is prepared through specific ratio and stirring processes.
It has achieved controllable condensation speed, high flexural strength, high early strength, high bond strength, and shrinkage, and is environmentally friendly and harmless to the body, reducing material costs.
Smart Images

Figure BDA0005252427460000151 
Figure BDA0005252427460000161 
Figure BDA0005252427460000162
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to an early-strength magnesium phosphate slag cement mortar and its preparation method. Background Technology
[0002] Magnesium phosphate cement (MPC), as a cutting-edge cementitious material, is composed of overburned magnesium oxide, soluble phosphates, and retarder, precisely proportioned and blended. The overburned magnesium oxide originates from magnesite calcined at 1700℃, forming a highly crystalline structure; the soluble phosphates provide the necessary acidic conditions and phosphate ions for the hydration process. MPC utilizes the principle of acid-base neutralization to tightly bind magnesium oxide particles with other components, constructing a high-strength, dense structure.
[0003] The blast furnace ironmaking process generates massive amounts of byproducts, including blast furnace slag, with annual emissions of blast furnace slag being staggering, accounting for more than half of the total metallurgical slag. This slag not only accumulates and causes environmental pollution and resource waste, but also hinders the healthy development of the industrial ecosystem. Blast furnace slag is rich in calcium oxide, silicon oxide, and alumina, and has advantages such as low cost, wide availability, and unique hydration properties, making its effective resource utilization urgently needed.
[0004] By integrating slag science into the magnesium phosphate cement system, an innovative magnesium phosphate slag cement mortar has been developed. Compared with traditional slag silicate cement, this material significantly improves early strength and flexural strength, accelerates the setting process, and achieves efficient utilization of industrial solid waste.
[0005] However, existing technologies have obvious limitations: on the one hand, although low-carbon concrete, as shown in patent CN117923863A, can reduce the heat of hydration and prevent cracking, it sacrifices early strength, prolongs the curing period, and is accompanied by large shrinkage deformation; on the other hand, although the early-strength green low-carbon magnesium phosphate concrete proposed in patent CN116621559A reduces cement usage and carbon emissions, the use of ammonium dihydrogen phosphate is accompanied by the release of ammonia, which threatens human health.
[0006] Therefore, developing a magnesium phosphate slag cement mortar and its preparation process that combines early strength characteristics with environmental advantages to overcome the above-mentioned defects has become an urgent technical problem to be solved. Summary of the Invention
[0007] The purpose of this invention is to provide an early-strength magnesium phosphate slag cement mortar and its preparation method. The prepared early-strength magnesium phosphate slag cement mortar has controllable setting speed, high flexural strength, high early strength, high bond strength, low shrinkage, and is harmless to the body and environmentally friendly.
[0008] To achieve the above objectives, the present invention provides an early-strength magnesium phosphate slag cement mortar, which is composed of the following raw materials in parts by weight: 60-540 parts of overburned magnesium oxide, 20-180 parts of potassium dihydrogen phosphate, 12-108 parts of slag powder, 4-36 parts of borax, 4-36 parts of sodium alginate, 85-765 parts of quartz sand, 0.4-3.6 parts of polypropylene fiber, 52-162 parts of water, and 0.3-2.7 parts of water-reducing agent.
[0009] Preferably, the calcium oxide content in the overburned magnesium oxide is <5%, and the specific surface area of the overburned magnesium oxide is 2500 cm². 2 / g, of which 50% is 10-200μm magnesium oxide and 50% is 200-800μm magnesium oxide.
[0010] Preferably, the purity of potassium dihydrogen phosphate is >98%, which is analytical grade AR.
[0011] Preferably, the slag powder is grade S105 with a density of not less than 2.8 g / m³. 3 Specific surface area not less than 700m² 2 / kg; Borax purity > 98%, analytical grade AR; Sodium alginate purity not less than 99%, analytical grade AR.
[0012] Preferably, the particle size of the quartz sand is 10 to 18 mesh.
[0013] Preferably, the polypropylene fiber has a length of 8-12 mm, a diameter of 10-20 μm, an aspect ratio of >600, a breaking elongation of 20-23%, and a tensile strength of >800 MPa.
[0014] Preferably, the water-reducing agent is a polyhydroxy acid water-reducing agent.
[0015] This invention also provides a method for preparing the early-strength magnesium phosphate slag cement mortar as described above, comprising the following steps:
[0016] Step S1: Weigh out the following ingredients by weight: overburned magnesium oxide, potassium dihydrogen phosphate, slag powder, borax, sodium alginate, quartz sand, polypropylene fiber, water, and water-reducing agent.
[0017] Step S2: Mix the overburned magnesium oxide, potassium dihydrogen phosphate, borax, sodium alginate, slag powder, and quartz sand to obtain a mixture. Pour the mixture into a mixer and stir slowly for 1-2 minutes to ensure that the dry materials are mixed evenly.
[0018] Step S3: After mixing the water-reducing agent and water evenly, add the mixture to the mixer and stir quickly for 1-2 minutes;
[0019] Step S4: After the mixture is stirred evenly, add the polypropylene fibers to the mixer to disperse the polypropylene fibers of different lengths evenly and avoid agglomeration. After adding all the polypropylene fibers, continue to stir rapidly for 1 to 2 minutes.
[0020] Step S5: After mixing, pour the mixture into a mold that has been brushed with release agent and press it down.
[0021] Step S6: After curing for 3 hours at an indoor temperature of 20±2℃ and a relative humidity of 40±5%, the mortar is demolded to obtain magnesium phosphate slag cement mortar.
[0022] Preferably, the stirring speed for slow stirring is 135–145 r / min, and the stirring speed for fast stirring is 275–295 r / min.
[0023] Therefore, the present invention employs the above-mentioned early-strength magnesium phosphate slag cement mortar and its preparation method, and the beneficial technical effects are as follows:
[0024] (1) The present invention uses magnesium phosphate slag cement mortar to replace slag silicate cement and combines it with mineral admixtures from industrial solid waste to prepare cement mortar. This not only reduces the amount of cement used and improves its flexural strength and early compressive strength, but also significantly reduces its material cost.
[0025] (2) The setting time can be controlled within 20 to 30 minutes. Compared with ordinary slag silicate cement, it can effectively solve the problem of long setting time of ordinary cement mortar. Compared with traditional magnesium phosphate cement, it delays the setting time and can effectively solve the problem that magnesium phosphate cement is limited in its practical engineering application due to its rapid setting and hardening.
[0026] (3) The present invention uses overburned magnesium oxide and potassium dihydrogen phosphate as raw materials for magnesium phosphate slag cement mortar, which can enhance the wear resistance of magnesium phosphate slag cement mortar, improve flexural strength and early compressive strength and reduce cement drying shrinkage; borax, sodium alginate and slag powder are used as retarder to fully extend the setting time of magnesium phosphate slag cement mortar and improve the early compressive strength of magnesium phosphate slag cement mortar. At the same time, some quartz sand and polypropylene fiber are filled to enhance the physical properties of magnesium phosphate slag cement mortar and improve the proportion and density of gel pores.
[0027] The magnesium phosphate slag cement mortar provided by this invention has advantages such as adjustable setting time, high flexural strength and early compressive strength, low shrinkage, high bond strength, and significantly reduced costs. It has very broad application prospects in building materials, comprehensive utilization of solid waste, and rapid structural repair and reinforcement. Detailed Implementation
[0028] The technical solution of the present invention will be further described below through embodiments.
[0029] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0030] Example 1
[0031] Raw material ratio for early-strength magnesium phosphate slag cement: 180g overburned magnesium oxide, 60g potassium dihydrogen phosphate, 12g borax, 12g sodium alginate, 36g slag powder, 255g quartz sand, 1.2g polypropylene fiber, 54g water, and 0.9g water-reducing agent.
[0032] The magnesium oxide used in this raw material is over-burned magnesium oxide obtained by calcination at 1700℃, with a calcium oxide content of 4% and a specific surface area of approximately 2500 cm². 2 / g, of which 50% is 10-200μm magnesium oxide and 50% is 200-800μm magnesium oxide; the purity of potassium dihydrogen phosphate is 99%, and it is analytical grade AR; the slag powder grade is S105, and the density is 2.8g / m³. 3 Specific surface area is 700m² 2 / kg; the purity of the borax used is 99%, analytical grade AR; the purity of the sodium alginate used is 99%, analytical grade AR; the particle size of the quartz sand is 10-18 mesh; the length of the polypropylene fiber is 8-12 mm, the diameter is 10-20 μm, the aspect ratio is >600, the elongation at break is 20-23%, the tensile strength is >800 MPa, and it has high strength, good elasticity, wear resistance, and corrosion resistance; the water-reducing agent is polyhydroxy acid water-reducing agent.
[0033] Preparation method:
[0034] (1) Mix overburned magnesium oxide, potassium dihydrogen phosphate, borax, sodium alginate, slag powder and quartz sand to obtain a mixture. Pour the mixture into a mixer and stir slowly for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed.
[0035] (2) After the water-reducing agent is mixed with water evenly, add it to the mixer and stir quickly for 1 to 2 minutes at a speed of 280 r / min;
[0036] (3) After the mixture is evenly stirred, add the polypropylene fiber into the mixer to disperse the polypropylene fiber of different lengths evenly and avoid agglomeration. After the polypropylene fiber is added, continue to stir quickly for 1 to 2 minutes at a speed of 280 r / min.
[0037] (4) After mixing, pour it into the mold that has been brushed with release agent and press it down;
[0038] (5) After curing at room temperature (T=20±2℃, RH=40±5%) for 3 hours, the mortar was demolded to obtain magnesium phosphate slag cement mortar.
[0039] Example 2
[0040] Raw material ratio for early-strength magnesium phosphate slag cement: 360g overburned magnesium oxide, 120g potassium dihydrogen phosphate, 24g borax, 24g sodium alginate, 72g slag powder, 510g quartz sand, 2.4g polypropylene fiber, 108g water, and 1.8g water-reducing agent.
[0041] The magnesium oxide used in this raw material is over-burned magnesium oxide obtained by calcination at 1700℃, with a calcium oxide content of 4% and a specific surface area of approximately 2500 cm². 2 / g, of which 50% is 10-200μm magnesium oxide and 50% is 200-800μm magnesium oxide; the purity of potassium dihydrogen phosphate is 99%, and it is analytical grade AR; the slag powder grade is S105, and the density is 2.8g / m³. 3 Specific surface area is 700m² 2 / kg; the purity of the borax used is 99%, analytical grade AR; the purity of the sodium alginate used is 99%, analytical grade AR; the particle size of the quartz sand is 10-18 mesh; the length of the polypropylene fiber is 8-12 mm, the diameter is 10-20 μm, the aspect ratio is >600, the elongation at break is 20-23%, the tensile strength is >800 MPa, and it has high strength, good elasticity, wear resistance, and corrosion resistance; the water-reducing agent is polyhydroxy acid water-reducing agent.
[0042] Preparation method:
[0043] (1) Mix overburned magnesium oxide, potassium dihydrogen phosphate, borax, sodium alginate, slag powder and quartz sand to obtain a mixture. Pour the mixture into a mixer and stir slowly for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed.
[0044] (2) After the water-reducing agent is mixed with water evenly, add it to the mixer and stir quickly for 1 to 2 minutes at a speed of 280 r / min;
[0045] (3) After the mixture is stirred evenly, add the polypropylene fibers to the mixer to disperse the polypropylene fibers of different lengths evenly and avoid agglomeration. After adding all the polypropylene fibers, continue to stir rapidly for 1 to 2 minutes at a speed of 280 r / min.
[0046] (4) After mixing, pour it into the mold that has been brushed with release agent and press it down.
[0047] (5) After curing at room temperature (T=20±2℃, RH=40±5%) for 3 hours, the mortar was demolded to obtain magnesium phosphate slag cement mortar.
[0048] Example 3
[0049] Raw material ratio for early-strength magnesium phosphate slag cement: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g borax, 36g sodium alginate, 108g slag powder, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0050] The magnesium oxide used in this raw material is over-burned magnesium oxide obtained by calcination at 1700℃, with a calcium oxide content of 4% and a specific surface area of approximately 2500 cm². 2 / g, of which 50% is 10-200μm magnesium oxide and 50% is 200-800μm magnesium oxide; the purity of potassium dihydrogen phosphate is 99%, and it is analytical grade AR; the slag powder grade is S105, and the density is 2.8g / m³. 3 Specific surface area is 700m² 2 / kg; the purity of the borax used is 99%, analytical grade AR; the purity of the sodium alginate used is 99%, analytical grade AR; the particle size of the quartz sand is 10-18 mesh; the length of the polypropylene fiber is 8-12 mm, the diameter is 10-20 μm, the aspect ratio is >600, the elongation at break is 20-23%, the tensile strength is >800 MPa, and it has high strength, good elasticity, wear resistance, and corrosion resistance; the water-reducing agent is polyhydroxy acid water-reducing agent.
[0051] Preparation method:
[0052] (1) Mix overburned magnesium oxide, potassium dihydrogen phosphate, borax, sodium alginate, slag powder and quartz sand to obtain a mixture. Pour the mixture into a mixer and stir slowly for 1 to 2 minutes at a speed of 140 r / min to make the dry materials evenly mixed.
[0053] (2) After the water-reducing agent is mixed with water evenly, add it to the mixer and stir quickly for 1 to 2 minutes at a speed of 280 r / min;
[0054] (3) After the mixture is stirred evenly, add the polypropylene fibers to the mixer to disperse the fibers of different lengths evenly and avoid agglomeration. After adding all the polypropylene fibers, continue to stir rapidly for 1 to 2 minutes at a speed of 280 r / min.
[0055] (4) After mixing, pour it into the mold that has been brushed with release agent and press it down;
[0056] (5) After curing at room temperature (T=20±2℃, RH=40±5%) for 3 hours, the mortar was demolded to obtain magnesium phosphate slag cement mortar.
[0057] Comparative Example 1:
[0058] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g sodium alginate, 108g slag powder, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0059] Compared with Example 3, Comparative Example 1 differs in that it does not contain borax in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is consistent with that of Example 3.
[0060] Compared with Example 3, the cement mortar provided in this comparative example lacks borax, which leads to a shorter setting time, faster hydration reaction, and concentrated heat release, which will have an adverse effect on the stability and strength development of the cement mortar.
[0061] Comparative Example 2:
[0062] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g borax, 108g slag powder, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0063] Compared with Example 3, Comparative Example 2 differs in that it does not contain sodium alginate in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is consistent with that of Example 3.
[0064] Compared to Example 3, the cement mortar provided in this comparative example lacks sodium alginate, which leads to a shorter setting time and a decrease in early strength. Furthermore, as a potential environmentally friendly alternative, the absence of sodium alginate may mean the continued use of retarders that pose potential risks to the environment and health, which could adversely affect the strength of the cement mortar and environmental protection.
[0065] Comparative Example 3:
[0066] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g borax, 36g sodium alginate, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0067] Compared with Example 3, Comparative Example 3 differs in that the raw material components do not contain slag powder, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is the same as in Example 3.
[0068] Compared with Example 3, the cement mortar provided in this comparative example lacks slag powder, which will result in a shorter setting time, reduced fluidity and density, and adversely affect its mechanical properties and durability, especially compressive strength.
[0069] Comparative Example 4:
[0070] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 108g slag powder, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0071] Compared to Example 3, Comparative Example 4 differs in that it does not contain borax and sodium alginate in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is consistent with that of Example 3.
[0072] Compared with Example 3, the cement mortar provided in this comparative example lacks borax and sodium alginate, which will result in a shorter setting time, reduced early strength, poorer durability, and excessively concentrated heat release, which will have an adverse effect on its mechanical properties and strength development.
[0073] Comparative Example 5:
[0074] Raw material ratio: 540g of overburned magnesium oxide, 180g of potassium dihydrogen phosphate, 765g of quartz sand, 3.6g of polypropylene fiber, 162g of water, and 2.7g of water-reducing agent.
[0075] Compared with Example 3, Comparative Example 5 differs in that it does not contain borax, sodium alginate, and slag powder in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is the same as in Example 3.
[0076] Compared with Example 3, the cement mortar provided in this comparative example lacks borax, sodium alginate and slag powder, which will result in a shorter setting time, reduced early strength, poorer durability, excessively concentrated heat release, reduced environmental adaptability, and increased cost due to the lack of slag powder.
[0077] Comparative Example 6:
[0078] Raw material ratio: 540g of overburned magnesium oxide, 180g of potassium dihydrogen phosphate, 765g of quartz sand, 162g of water, and 2.7g of water-reducing agent.
[0079] Compared with Example 3, Comparative Example 6 differs in that it does not contain borax, sodium alginate, slag powder, and polypropylene fiber in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is consistent with that of Example 3.
[0080] Compared with Example 3, the cement mortar provided in this comparative example does not contain retarders and fibers, which will result in a shorter setting time, hindered early strength development, reduced crack resistance and fatigue resistance, and adverse effects on setting time, early strength, durability, etc.
[0081] Comparative Example 7:
[0082] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g borax, 36g sodium alginate, 108g slag powder, 765g river sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0083] Compared with Example 3, Comparative Example 7 differs in that ordinary river sand is used instead of an equal amount of quartz sand in the raw materials, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is the same as in Example 3.
[0084] Compared with Example 3, although ordinary river sand can replace quartz sand in the cement mortar provided in this comparative example, the fluidity of ordinary river sand is not as good as that of quartz sand, which will lead to a decrease in the fluidity of cement mortar. In addition, the strength of ordinary river sand is not as high as that of quartz sand, which will affect the strength of cement mortar and reduce its mechanical properties.
[0085] Comparative Example 8:
[0086] Raw material ratio: 540g overburned magnesium oxide, 180g ammonium dihydrogen phosphate, 36g borax, 36g sodium alginate, 108g slag powder, 765g quartz sand, 3.6g polypropylene fiber, 162g water, and 2.7g water-reducing agent.
[0087] Compared with Example 3, Comparative Example 8 differs in that: ammonium dihydrogen phosphate is used instead of an equal amount of potassium dihydrogen phosphate in the raw materials, while the mass ratio of the remaining components is the same as in Example 3. The preparation method is the same as in Example 3.
[0088] Compared with Example 3, although ammonium dihydrogen phosphate in the cement mortar provided in this comparative example can be used to replace potassium dihydrogen phosphate in the preparation of magnesium phosphate cement mortar, ammonium dihydrogen phosphate will release some ammonia gas during the reaction process. Ammonia gas is a harmful gas that can harm the environment and human health.
[0089] Comparative Example 9:
[0090] Raw material ratio: 540g overburned magnesium oxide, 180g potassium dihydrogen phosphate, 36g borax, 36g sodium alginate, 108g slag powder, 765g quartz sand, 162g water, and 2.7g water-reducing agent.
[0091] Compared with Example 3, Comparative Example 9 differs in that it does not contain polypropylene fiber in its raw material components, while the remaining components and their mass ratios are the same as in Example 3. The preparation method is the same as in Example 3.
[0092] Compared with Example 3, the cement mortar provided in this comparative example does not contain polypropylene fibers, which will lead to a decrease in the flexural strength and compressive strength of the cement mortar, and its crack resistance and toughness will also be affected to varying degrees.
[0093] Comparative Example 10:
[0094] Raw material ratio: 540g of overburned magnesium oxide (70% of 10-200μm and 30% of 200-800μm), 180g of potassium dihydrogen phosphate, 36g of borax, 36g of sodium alginate, 108g of slag powder, 765g of quartz sand, 3.6g of polypropylene fiber, 162g of water, and 2.7g of water-reducing agent.
[0095] Compared with Example 3, Comparative Example 10 differs in that the proportion of different particle sizes of overburned magnesium oxide in the raw material components is different (70% for 10-200 μm and 30% for 200-800 μm), while the mass ratio of the remaining components is the same as in Example 3. The preparation method is the same as in Example 3.
[0096] Compared with Example 3, the cement mortar provided in this comparative example uses overburned magnesium oxide with different particle sizes (70% of which are 10-200μm and 30% are 200-800μm). The increase in smaller magnesium oxide particles will lead to a faster hydration reaction rate and a shorter setting time, which will have an adverse effect on the workability of construction and the early strength development.
[0097] Comparative Example 11:
[0098] Raw material ratio: 540g of overburned magnesium oxide (90% of 10-200μm and 10% of 200-800μm), 180g of potassium dihydrogen phosphate, 36g of borax, 36g of sodium alginate, 108g of slag powder, 765g of quartz sand, 3.6g of polypropylene fiber, 162g of water, and 2.7g of water-reducing agent.
[0099] Compared with Example 3, Comparative Example 11 differs in that the proportion of different particle sizes of overburned magnesium oxide in the raw material components is different (90% for 10-200 μm and 10% for 200-800 μm), while the mass ratio of the remaining components is the same as in Example 3. The preparation method is the same as in Example 3.
[0100] Compared with Example 3, the cement mortar provided in this comparative example uses overburned magnesium oxide with different particle sizes (90% of which are 10-200μm and 10% of which are 200-800μm). Compared with Comparative Example 10, the proportion of smaller magnesium oxide particles in this comparative example is greater, which will lead to a faster hydration reaction rate and a shorter setting time, which will have an adverse effect on the workability of construction and the early strength development.
[0101] Comparative Example Twelve:
[0102] Raw material ratio: 540g of overburned magnesium oxide (30% of 10-200μm and 70% of 200-800μm), 180g of potassium dihydrogen phosphate, 36g of borax, 36g of sodium alginate, 108g of slag powder, 765g of quartz sand, 3.6g of polypropylene fiber, 162g of water, and 2.7g of water-reducing agent.
[0103] Compared with Example 3, Comparative Example 12 differs in that the proportions of different particle sizes of overburned magnesium oxide in the raw material components are different (30% for 10-200 μm and 70% for 200-800 μm), while the mass ratios of the remaining components are the same as in Example 3. The preparation method is the same as in Example 3.
[0104] Compared with Example 3, the cement mortar provided in this comparative example uses overburned magnesium oxide with different particle sizes (30% of which are 10-200μm and 70% are 200-800μm). The increase in the number of magnesium oxide particles with larger particle sizes will lead to a decrease in its fluidity and an increase in the number of large pores inside the mortar, which will affect the pore structure and density of its hardened body and have an adverse effect on its mechanical properties.
[0105] Comparative Example 13:
[0106] Raw material ratio: 540g of overburned magnesium oxide (10% of 10-200μm and 90% of 200-800μm), 180g of potassium dihydrogen phosphate, 36g of borax, 36g of sodium alginate, 108g of slag powder, 765g of quartz sand, 3.6g of polypropylene fiber, 162g of water, and 2.7g of water-reducing agent.
[0107] Compared with Example 3, Comparative Example 13 differs in that the proportions of different particle sizes of overburned magnesium oxide in the raw material components are different (10-200 μm accounts for 10%, and 200-800 μm accounts for 90%), while the mass ratios of the remaining components are the same as in Example 3. The preparation method is the same as in Example 3.
[0108] Compared with Example 3, the cement mortar provided in this comparative example uses overburned magnesium oxide with different particle sizes (10% of 10-200μm and 90% of 200-800μm). Compared with Comparative Example 12, the proportion of larger magnesium oxide particles in this comparative example is greater, which leads to lower fluidity and more large pores inside the mortar, affecting the pore structure and density of the hardened body and having an adverse effect on its mechanical properties.
[0109] The products prepared in Examples 1 to 3 and Comparative Examples 1 to 13 were subjected to setting time, compressive strength and flexural strength tests, respectively. The compressive strength and flexural strength at setting time and 1d, 7d and 28d were measured.
[0110] The test results are as follows:
[0111] Table 1. Results of setting time
[0112] Specimen Number Condensation time / min Example 1 19 Example 2 23 Example 3 28 Comparative Example 1 13 Comparative Example 2 16 Comparative Example 3 17 Comparative Example 4 11 Comparative Example 5 5 Comparative Example 6 4 Comparative Example 7 20 Comparative Example 8 22 Comparative Example 9 20 Comparative Example 10 18 Comparative Example 11 15 Comparative Example Twelve 22 Comparative Example Thirteen 23
[0113] Table 2 Flexural strength results
[0114]
[0115]
[0116] Table 3 Compressive strength results
[0117] Specimen Number Compressive strength (1d) / MPa Compressive strength (7d) / MPa Compressive strength (28d) / MPa Example 1 20.9 31.8 50.6 Example 2 23.6 32.5 55.7 Example 3 28.4 37.1 64.9 Comparative Example 1 21.6 30.5 48.7 Comparative Example 2 22.3 31.4 50.2 Comparative Example 3 22.7 31.0 52.6 Comparative Example 4 20.4 31.7 51.5 Comparative Example 5 21.2 30.3 50.8 Comparative Example 6 20.1 29.8 49.3 Comparative Example 7 24.5 33.7 56.2 Comparative Example 8 24.8 34.1 55.3 Comparative Example 9 23.7 32.2 54.8 Comparative Example 10 24.4 33.6 54.7 Comparative Example 11 25.6 35.7 58.3 Comparative Example Twelve 23.1 34.3 52.8 Comparative Example Thirteen 22.6 32.9 51.5
[0118] Table 4 Standard for compressive strength of slag silicate cement
[0119]
[0120] Table 5 Standard for Flexural Strength of Slag Silicate Cement
[0121]
[0122] In summary, as can be seen from Example 3, the setting time, compressive strength, and flexural strength of the early-strength magnesium phosphate slag cement mortar prepared by the present invention are significantly improved compared with conventional production methods.
[0123] Therefore, the present invention uses the above-mentioned early-strength magnesium phosphate slag cement mortar and its preparation method. The prepared early-strength magnesium phosphate slag cement mortar has controllable setting speed, high flexural strength, high early strength, high bond strength, low shrinkage, and is harmless to the body and environmentally friendly.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. An early-strength magnesium phosphate slag cement mortar, characterized in that: The invention is composed of the following raw materials in parts by weight: 60-540 parts of over-burned magnesium oxide, 20-180 parts of potassium dihydrogen phosphate, 12-108 parts of slag powder, 4-36 parts of borax, 4-36 parts of sodium alginate, 85-765 parts of quartz sand, 0.4-3.6 parts of polypropylene fiber, 52-162 parts of water and 0.3-2.7 parts of water reducing agent.
2. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The content of calcium oxide in the overburned magnesium oxide is less than 5%, and the specific surface area of the overburned magnesium oxide is 2500cm 2 / g, of which 10-200μm magnesium oxide is 50%, and 200-800μm magnesium oxide is 50%.
3. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The purity of potassium dihydrogen phosphate is greater than 98%, which is analytical grade AR.
4. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The slag powder grade is S105, and the density is not less than 2.8g / m 3 , with a specific surface area of not less than 700m 2 / kg; the purity of borax is greater than 98%, which is analytically pure AR; the purity of sodium alginate is not less than 99%, which is analytically pure AR.
5. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The particle size of quartz sand is 10 to 18 mesh.
6. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The length of the polypropylene fiber is 8-12 mm, the diameter is 10-20 μm, the aspect ratio is greater than 600, the elongation at break is 20-23%, and the tensile strength is greater than 800 MPa.
7. The early-strength magnesium phosphate slag cement mortar according to claim 1, characterized in that: The water reducing agent is a polyhydroxy acid water reducing agent.
8. A method for preparing the early-strength magnesium phosphate slag cement mortar according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, weighing burnt magnesium oxide, potassium dihydrogen phosphate, slag powder, borax, sodium alginate, quartz sand, polypropylene fiber, water, and water reducing agent in parts by weight; Step S2, mixing overburned magnesium oxide, potassium dihydrogen phosphate, borax, sodium alginate, slag powder and quartz sand to obtain a mixed material, pouring the mixed material into a mixer and slowly stirring for 1 to 2 minutes to mix the dry materials evenly; Step S3, after mixing the water reducing agent and water evenly, add them into a mixer and stir rapidly for 1 to 2 minutes; Step S4, after the mixed material is stirred evenly, polypropylene fibers are added into the mixer to evenly disperse the polypropylene fibers of different lengths to avoid agglomeration. After the polypropylene fibers are added, continue to stir rapidly for 1 to 2 minutes; Step S5: After the stirring is completed, pour it into a mold that has been brushed with a release agent and compact it; Step S6, under the conditions of indoor temperature of 20±2° C. and relative humidity of 40±5%, curing for 3 hours and then demoulding to obtain magnesium phosphate slag cement mortar.
9. The method for preparing an early-strength magnesium phosphate slag cement mortar according to claim 8, characterized in that: The speed of slow stirring is 135-145r / min, and the speed of fast stirring is 275-295r / min.
Citation Information
Patent Citations
Low-carbon concrete and preparation method thereof
CN117923863A
High-early-strength magnesium phosphate concrete and preparation method thereof
CN101386518A
Magnesium phosphate cement prepared by using magnesium oxide byproduct in process of extracting lithium carbonate from salt lake
CN102390943A
Water-resistant magnesium phosphate cement and application thereof
CN104591570A
Magnesium phosphate cement base fiber composite material and preparation method thereof
CN110803912A
Cited By
Magnesium phosphate fire-resistant composite coating based on industrial solid waste and preparation method of magnesium phosphate fire-resistant composite coating
CN120574494A
A magnesium phosphate fire-resistant composite coating based on industrial solid waste and a preparation method thereof
CN120574494B
Nanometer modified fiber reinforced 3D printing magnesium phosphate cement-based material as well as preparation method and application thereof
CN120965267A